CO2 and temperature effects on morphological and physiological traits affecting risk of drought-induced mortality. (26th April 2018) - Duan, Honglang; Chaszar, Brian; Lewis, James D; Smith, Renee A; Huxman, Travis E; Tissue, David T
Abstract: Despite a wealth of eco-physiological assessments of plant response to extreme drought, few studies have addressed the interactive effects of global change factors on traits driving mortality. To understand the interaction between hydraulic and carbon metabolic traits influencing tree mortality, which may be independently influenced by atmospheric [CO2 ] and temperature, we grew Eucalyptus sideroxylon A. Cunn. ex Woolls from seed in a full-factorial [CO2 ] (280, 400 and 640 μmol mol −1, C p, C a and C e, respectively) and temperature (ambient and ambient +4 °C, T a and T e, respectively) experiment. Prior to drought, growth across treatment combinations resulted in significant variation in physiological and morphological traits, including photosynthesis ( A sat ), respiration ( R d ), stomatal conductance, carbohydrate storage, biomass and leaf area (LA). C e increased A sat, LA and leaf carbohydrate concentration compared with C a, while C p generated the opposite response; T e reduced R d . However, upon imposition of drought, T e hastened mortality (9 days sooner compared with T a ), while C e significantly exacerbated drought stress when combined with T e . Across treatments, earlier time-to-mortality was mainly associated with lower (more negative) leaf water potential (Ψl ) during the initial drought phase, along with higher water loss across the first 3 weeks of water limitation. Among many variables, Ψl was more important than carbon status in predicting time-to-mortality across treatments, yet leaf starch was associated with residual variation within treatments. These results highlight the need to carefully consider the integration, interaction and hierarchy of traits contributing to mortality, along with their responses to environmental drivers. Both morphological traits, which influence soil resource extraction, and physiological traits, which affect water-for-carbon exchange to the atmosphere, must be considered to adequately predict plant response to drought. Researchers have struggled with assessing the relative importance of hydraulic and carbon metabolic traits in determining mortality, yet an integrated trait, time-dependent framework provides considerable insight into the risk of death from drought for trees.